2020
DOI: 10.5194/aab-63-409-2020
|View full text |Cite
|
Sign up to set email alerts
|

DNA analysis of the Russian populations of Aberdeen Angus, Hereford and Belgian Blue cattle

Abstract: Abstract. The use of specialized meat breeds in cattle breeding programs is considered very promising for improving herds' productivity. However, in animal genotype, along with genes that positively affect the productivity signs, there are genes whose mutations, known as genetic defects, negatively affect the health of animals. The aim of the study was the screening of the Russian populations of Aberdeen Angus, Hereford and Belgian Blue cattle on gene mutations associated with the genetic defects of arthrogryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The study of the meat cattle genetic defects since 2017 has shown the existence of animals carrying the mutant alleles linked with the appearance of inherited diseases in their genotypes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the meat cattle genetic defects since 2017 has shown the existence of animals carrying the mutant alleles linked with the appearance of inherited diseases in their genotypes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the study, we assumed that the Hereford breed was free from harmful mutations associated with congenital pathologies [ 24 ]. However, the present investigations have shown the contrasting fact: Among the investigated populations, the single animal carriers of MSUD, ICM, HY and CWH have been revealed ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA were extracted from the available biomaterial of the animals (skin, sperm, milk, and blood) by methods traditionally used in the lab of genetics and genomics of cattle at L.K. Ernst Federal Research Center for Animal Husbandry (Dubrovitsy, Moscow, Russia) [22].…”
Section: Methodsmentioning
confidence: 99%
“…The genotyping methods were chosen based on the structures of the studied mutations. Due the presence of the small deletion for nt821(del11) genotyping, we used the allele-specific PCR method (AS-PCR) [22]. For F94L polymorphism diagnostics, we chose the PCR-RFLP (PCR with the subsequent analysis of restriction fragments length polymorphism) method due the existence of a mutation area recognition site for the TaqI restriction endonuclease site in the DNA.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported by Meyermans et al (2022) that the 11-deletion (known as nt821(del11)) occurs in the MSTN sequence of BB cattle, which leads to a premature stopcodon and dysfunctional protein. However, several reports found that a higher birth weight leads to a higher risk of dystocia (Druet et al, 2014;Konovalova et al, 2021Konovalova et al, , 2020Simões and Stilwell, 2021). To reduce the effect of dystocia, almost all the purebred BB offspring in Indonesia were delivered using a cesarean section procedure.…”
Section: Growth Performance Of Bb Cattle and Its Crossbred Offspringmentioning
confidence: 99%